High Powered Assistants: Women in Feminized Secretarial Positions at the League of Nations and the United Nations c. 1920–1975 - Piguet, Myriam (Almagest, 2025)
Abstract Applying a history from below approach, this article extends the history of international organizations. It seeks to broaden the definition of International Thought by including the contribution of subsidiary staff in the intellectual production of international organizations (IOs), with a special focus on women. This article maps the involvement of women in the standardization of bureaucratic practices in IOs secretariats. This approach aligns with the recent research on international organizations which views IOs as actors of International Thought and not merely its executors. Scholars have shown that the development of international bureaucracy throughout the twentieth century has contributed to a renewed examination of International Thought. This has directed the focus on IOs’ technical, rather than political, aspects. This transformation, in turn, increased the influence of its technical aspects alongside the political.